Pola Komunikasi Orang Tua Terhadap Anak di Pagerungan Besar Sumenep - Rayendra Imrona Yanji; Yohandi; Edy Supriyono (Fakultas Dakwah Universitas Ibrahimy, 2024)
This research discusses communication patterns that occur between parents and children in Pagerungan Besar Village, Sapeken District, Regency, with the main problem being how parents communicate with children in an effort to build positive morals. The aim is to describe the form of communication between parents and children in Pagerungan Besar village, Sumenep. This type of research is descriptive qualitative. The research approach used is an interpersonal communication approach. The research subject is Mr Muhnadin's family. Data collection methods use observation, interview and documentation techniques. The data analysis technique used is source triangulation. The results of the research show that there are two forms of communication used by parents to instill morals in children, namely first, linear, interactional and transactional communication patterns. These three patterns cannot be separated because they are interconnected with one another. Second, the dialogic interpersonal communication model used by parents towards their children to create an atmosphere that is not boring so that children easily understand what the parents want. One of the meanings of the resulting communication pattern for children is increasing the child's motivation so that the child gets achievements at school and the second is having a positive personality in everyday life so that it does not bother parents.